Pengaruh Efektivitas Penerapan Sistem Informasi Akuntansi, Kesesuaian Tugas dan Kenyamanan Fisik Pada Kinerja Karyawan LPD - Widiantari, Ni Putu; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 29 No 1 (2019), 2019)
This study aims to obtain evidence regarding the factors that influence the performance of employees in LPD in Badung Regency, which include the effectiveness of the application of accounting information systems, suitability of tasks with information technology, and physical comfort. The study was conducted in the LPD of Badung Regency with a population of 366 people. The sample is determined using a solvin formula which is 191 people. The respondents used in this study were employees who were directly involved with information technology, namely the chairman of the LPD, treasurer, and administration. Multiple linear regression method is a data analysis technique used in this study. The research obtained results that the effectiveness of the application of information technology has a positive influence on employee performance. The suitability of the task with information technology and Physical comfort also shows a positive influence on employee performance. Keywords : Performance; Effectiveness; Tasks Suitability; Comfortness.